Estratégia reprodutiva do peixe hermafrodita mussum, Synbranchus marmoratus Osteichthyes, Synbranchidae em um açude do Rio Grande do Norte, Brasil - Barros, Nirlei Hirachy Costa (2012)
Reproductive strategy of the hermaphrodite fish the marbled swamp eel, Synbranchus marmoratus (Bloch, 1795) (Osteichthyes: Synbranchidae) was investigated in the Marechal Dutra reservoir, Acari, Rio Grande do Norte, using fish samples captured monthly during the period of July 2010 to July 2011. The limnological parameters and rainfall were verified. The captured fish specimens were numbered, weighed, measured, dissected and their gonads and liver were removed, weighed and identified as to sex and developmental stages of gonads. The length-weight relationship was determined for grouped sex. The size of first gonadal maturation, gonadosomatic index (GSI), condition factor (K) and hepatosomatic index (HSI) were calculated. The development stages of the gonads were investigated using macroscopic and histological techniques, besides the fecundity and reproductive period. The macroscopic characteristics and the histological development of gonads confirmed the four different sexual types in the sampled population: primary males, females, intersex and secondary males. The secondary males were bigger and heavier than all the other types. This species showed a negative allometric growth with a higher increase in length than weight. The size at which 50% of the females began the process of gonadal maturation was 43.5 cm of total length, and for secondary males it was 58.5 cm. Condition factor showed two peaks in February and in April 2011. IGS indicated a reproductive period from July to September 2010 and was negatively correlated with the condition factor and rainfall. IGS showed a negative correlation when compared with the condition factor and the rainy season. HSI was highest in February ad lowest in December. The reproductive period of this species occurs between the end of the rainy season and the beginning of the dry season. S. marmoratus presents a seasonal reproductive strategy which optimizes its reproductive success under the semiarid climatic conditions